The Goat as a Model for studies of pneumonic pasteurellosis caused by Pasteurella Multocida - Saad, Mohd Zamri; Abd Wahid, Mohd Effendy; Mat Amin, Maswati; Salim, Nadzri; Abdul Rahman, Sheikh Omar (Elsevier, 1996)
A model of pneumonic pasteurellosis has been established in goats using Pasteurella multocida harvested from pneumonic lungs of goats (types A and D), rabbits (type A) and sheep (type D). The resultant infections were acute, subacute or chronic. The gross and histological lesions of the subacute and chronic infections were typical of pneumonic pasteurellosis. P. multocida type D produced significantly (P<0.01) more severe lesions when compared with other isolates. There were strong correlations between the clinical signs and the severity of lesions.